Analysis of Sharia Bank Financial Performance in the Digital Era - Mahfuz, Muhammad (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
The digital era has brought significant changes in various industrial sectors, including the banking industry. Sharia banks as one of the financial institutions that adopt sharia principles are also not immune from the impact of this change. This article aims to analyze the financial performance of Islamic banks in the digital era by focusing on aspects such as technological innovation, changes in consumption patterns, as well as the impact on profitability and efficiency. The research method used is descriptive analysis with a quantitative approach, using secondary data from financial reports of Islamic banks registered with the OJK. The research results show that digitalization contributes positively to the financial performance of Islamic banks, although there are challenges that need to be overcome. It is hoped that these findings will provide insight for practitioners and academics in understanding the dynamics of Islamic bank financial performance amidst technological advances.